Use of Based Learning Media Motion Graphic Animation Video to Enhance Social Studies Learning Outcomes - Tetep Tetep; Alni Dahlena (Social Studies Conference Proceedings, 2022)
Problems in learning activities and the impact on social studies learning outcomes are still unsatisfactory. This is because students are getting used to using digital media in carrying out various activities. However, teachers have not been able to innovate and take advantage of it, especially in learning to motivate students to be more active by using learning media and increasing social studies learning outcomes. This study aimed to determine the effect of using animated video-based learning media on motion graphics on social studies learning outcomes. This type of Research uses a quantitative approach with a quasi-experimental method, and the research design is a non-equivalent control group design with pre-test and post-test. The population of this Research is the seventh-grade students of SMP Negeri 2 Cisewu. The samples were taken by purposive sampling technique, namely the experimental and control classes. The instruments used in this study were in the form of tests and non-test. Based on the results of the statistical analysis of the initial ability between the experimental and control classes, there was no significant difference. As for the results of the final test, it can be seen that there is a difference between the experimental class and the control class. The control class has lower learning outcomes than the experimental class, which uses motion graphic animation video learning media with very high improvement categories. The use of motion graphic animation videos learning media also received a good response from students. This is evidenced by students' enthusiasm for ongoing learning, which impacts increasing social studies learning outcomes.